Contextual Variability in Personality From Significant–Other Knowledge and Relational Selves - Andersen, Susan M.; Tuskeviciute, Rugile; Przybylinski, Elizabeth; Ahn, Janet N.; Xu, Joy H. (Frontiers in Psychology, 2016)
We argue that the self is intrinsically embedded in an interpersonal context such that it varies in IF-THEN terms, as the relational self. We have demonstrated that representations of the significant other and the relationship with that other are automatically activated by situational cues and that this activation affects both experienced and expressed aspects of the self and personality. Here, we expand on developments of the IF–THEN cognitive-affective framework of personality (CAPS, Mischel & Shoda, 1995), by extending it to the domain of interpersonal relationships at the dyadic level (Andersen & Chen, 2002). Going beyond Mischel’s early research (Mischel, 1968), our framework combines social cognition and learning theory with a learning-based psychodynamic approach, which provides the basis for extensive research on the social-cognitive process of transference and the relational self as it arises in everyday social interactions (Andersen & Cole, 1990), evidence from which contributes to a modern conceptualization of personality that emphasizes the centrality of the situation.